Penilaian Keberhasilan Pos Upaya Kesehatan Kerja Wisata Hutan Pinus Mangunan, D.I. Yogyakarta - Agustin, Helfi; Ruliyandari , Rochana; Ridwan Ansari, Muhammad; Kodriati, Nurul (LPPM Hang Tuah Pekanbaru, 2024)
Puskesmas Dlingo has initiated Basic Occupational Health Services (BOHS) in the Mangunan forest tourism village since 2019. To develop the BOHS, the program manager of the BOHS at the health centre is to carry out mentoring functions during the initiation of formation, coaching tasks after the UKK post is formed, and monitor and evaluate the implementation of the UKK post. Since its establishment, this UKK post has never been assessed for its activity. The purpose of this study was to assess BOHS in Mangunan forest tourism. This study is qualitative research with a case study approach. The informants consisted of nine people: the BOHS program manager and the head of the Puskesmas Dlingo, workers/cadres, the BOHS supervisor from the Bantul Regency Health Office, and the tourism manager. All informants were selected purposively. Data were collected using in-depth interview methods and analyzed thematically. The components to assess are the number of cadres, integrated health service activities, promotive and preventive activities, BOHS facilities, recording and reporting, and revolving funds. The study found that all components indicate the BOHS is currently less active and tends to be inactive. Puskesmas policies are needed through budgets, necessary training in occupational health empowerment, and networking.